Definition of crisis state of enterprises - V.M. Danich; N.O. Parkhomenko (Marketing i Menedžment Innovacij, 2013)
The aim of the article. The aim of the article is to determine the critical situation at the enterprise for early diagnosis and prediction the crises; development of methodical approaches to the solution of problems in this sphere taking into account the prediction of financial crisis for enterprises of different branches of the business activity. The results of analysis. The approaches to the definition of crisis have been analyzed in the article. The considered approaches to the definition of the crisis make it possible to formulate the definition of crisis state of an enterprise. In order to identify the crisis state of enterprises it is suggested to use comparative analysis. The evaluation and the analysis of crisis state are performed in five blocks. First phase of analysis of the crisis defines the probability of the expression of the crisis at the enterprise. It includes criteria for evaluation of generalized probability bankruptcy and comprehensive economic analysis of the efficiency of industrial and financial activity. This analysis is supplied by coefficient, rating and factor methods of diagnosis of crisis. In the practice of prediction of crisis at the enterprise it is proposed to use the model of automata theory. At the second stage it is proposed to identify the main causes of the onset of crisis. The causal connections of a crisis are required sources of forming the necessary information to determine the probability of a crisis in the company. The information database to form a forecasting model of crisis was defined. The next stage in the analysis of the crisis is analysis of costs of the crisis. It has been propose for involves the assessment of the loss, determining the amount of liabilities, estimates of expected financial impact of a crisis. Analyze available resources that can be produced to prevent or overcome the crisis. The analysis of crisis is the use of suggested methodological approach that makes it possible to choose the anti-crisis business strategy and to evaluate consequences of the crisis for certain scenarios. Result of forecasting of crises has a specific meaning to the strategy of the company, and forecasting tool must meet certain requirements to provide qualitative prediction. Prediction of crisis allows monitoring, evaluation and analysis of the company; identify change trends of factors internal and external environment; identify negative and positive effects that can to influence the process of development. Conclusions and directions of further researches. As a result it has been determined that the crisis caused by the emergence different spheres of activities. Such crises are identified the results of activity. Since, the analysis of the crisis illustrates the importance of the crisis prediction. This analysis reveals the probability of the crisis in the company, determines the causes of the crisis. In further researches the main list of the indicators of crisis for enterprises of different industries should be identified and a model of crisis prediction should be generated.